2000
DOI: 10.1203/00006450-200003000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pneumolysin on Rat Brain Ciliary Function: Comparison of Brain Slices with Cultured Ependymal Cells

Abstract: This study compares two models for examining ependymal ciliary function: rat brain slices cut from the fourth ventricle and primary ependymal cells in culture. The cilia from both preparations were very reproducible; each preparation had cilia beating at a constant frequency of between 38 and 44 Hz. With the brain slices, ciliary stasis occurred after 5 d in culture. However, ependymal cells had fully functional cilia for up to 48 d in culture. The pneumococcal toxin, pneumolysin, caused a dose-dependent inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 11 publications
0
46
0
2
Order By: Relevance
“…That study reported a significant reduction in CBF almost immediately after exposure to RSV, with complete ciliostasis as early as 6 h post-infection [9]. In our experience the rapid onset of ciliostasis is frequently attributed to the presence of a toxin or to the nonphysiological nature of the carrier fluid; solutions with a low pH can cause rapid ciliostasis [18]. Another study reported that the addition of unwashed ultraviolet-irradiated RSV increased toxicity to HeLa cells, suggesting their viral preparation may have contained a toxic contaminant [13].…”
Section: Basal Cell Cultures Infected With Rsv Increase Secretion Of mentioning
confidence: 97%
“…That study reported a significant reduction in CBF almost immediately after exposure to RSV, with complete ciliostasis as early as 6 h post-infection [9]. In our experience the rapid onset of ciliostasis is frequently attributed to the presence of a toxin or to the nonphysiological nature of the carrier fluid; solutions with a low pH can cause rapid ciliostasis [18]. Another study reported that the addition of unwashed ultraviolet-irradiated RSV increased toxicity to HeLa cells, suggesting their viral preparation may have contained a toxic contaminant [13].…”
Section: Basal Cell Cultures Infected With Rsv Increase Secretion Of mentioning
confidence: 97%
“…Ciliated rat ependymal cells were grown using a method adapted from Wiebel and colleagues (Weibel et al, 1986) and described previously (Hirst et al, 2000).…”
Section: Ependymal Cell Culturementioning
confidence: 99%
“…Ependymal cilia also have been shown to play an important role in host defence against pathogens (Hirst et al, 2003;Hirst et al, 2000;Mohammed et al, 1999). In addition, a recent study (Sawamoto et al, 2006) has shown that ependymal cilia are responsible for the formation of gradients of CSF guidance molecules that direct neuroblast movement in the brain parenchyma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the vascular epithelial cells regulate the passage of molecules from blood to CSF and the ciliated ependyma has a similar function in the regulation of molecules from CSF to brain, it is reasonable to hypothesize that the effect of pneumolysin on each cell type will share common characteristics. Hirst et al have shown that pneumolysin is toxic to ciliated ependymal cells [2,3].…”
Section: Introductionmentioning
confidence: 99%